PENGEMBANGAN SISTEM INFORMASI PRODUKSI PADA PT. ALUMINA - Chandra Chandra; Orrick Oetomo; Fandi Halim; Sophya Hadini Marpaung (STMIK Budi Darma, 2019)
PT. Alumina is a company that provides aluminum production such as windows, doors, glass and so on in Medan city. Due to complexity and prone to errors when raw materials calculation and data for reports must be collected in advance which takes a long time so that hamper in preparing reports of cost of goods sold (HPP) and the current report. This product system information application can display the status of production process that serves to find out how far the process of work orders (SPK), material requirement planning, the length of time required for production, raw material receipt to know whether product is ready for production, production confirmation when the product is done, cost of goods sold (COGS) and other current reports. To solve the problems, writer has designed a production information systems using Microsoft Visual Basic 2012 to designing the visual and application, Microsoft SQL Server 2012 to manage the database and using Crystal Report 13.0.5 in the making of the reports. Writer also uses SDLC (System Development Life Cycle) method to help writer make a design for production information system applications so that the existing problems can be solved.Keywords: information system, production, production cycle